KONTRIBUSI SUB SEKTOR PERTANIAN DALAM PEREKONOMIAN DI KABUPATEN SIGI - Andi Pribadi; Alimudin Laapo; Dewi Nur Asih (Universitas Tadulako, 2019)
This study aimed to determine the contribution of the agricultural sub-sector in the economy of Sigi district, to determine the basis agricultural sector in Sigi district in prioritizing regional development in order to compete in the Central Sulawesi economy, and to analyze the growth of the agricultural sector and agricultural competitiveness in Sigi district. The largest contribution of the agricultural sector (51.58%) in generating the GRDP of Sigi district, during the year 2013-2017, occurred in 2014 while the lowest contribution (47.58%) occurred in 2017. The food crop sub-sector, despite experiencing declines in recent years, continues to make contribution to Sigi district GRDP. The agricultural sector shows an average LQ value of 1.49, which confirms that the agricultural sector is one of the basis sectors in Sigi Regency. The comparative advantage in the agricultural sector is strongly influenced by the plantation crop sub-sector and the food crop sub-sector with the average LQ values were 1.72 and 1.15, respectively. The shift share analysis of the provincial share component shows that the agricultural sector has a large contribution to the performance of Sigi economy which is influenced by the economic growth of Central Sulawesi Province as much as IDR 48.44 billions. The proportional shift component shows that the value of the agricultural sector is IDR -406.949 billion indicating that the economy of Sigi district specializes in the same sector and it grows slowly in the economy of Central Sulawesi Province. The differential shift component shows that the agriculture, forestry and fisheries sectors have competitive advantages with a value of IDR 1.30 billions.